Endothelial cell protein kinase G inhibits release of EDHF through a PKG-sensitive cation channel. - Dora, K; Garland, C; Kwan, H; Yao, X (2001)
The release of dilator agents from vascular endothelial cells is modulated by changes in cytosolic Ca(2+) concentration ([Ca(2+)](i)). In this study, we demonstrate the presence of a Ca(2+)-permeable cation channel in inside-out membrane patches of endothelial cells isolated from small mesenteric arteries. The activity of the channel is increased by KT-5823, a highly selective inhibitor of protein kinase G (PKG), while it is decreased by direct application of active PKG. Application of KT-5823 induces Ca(2+) influx in the endothelial cells isolated from small mesenteric arteries, and it also causes endothelium-dependent relaxations in isolated small mesenteric arteries. KT-5823-induced relaxations in small mesenteric arteries are greatly reduced by 35 mM K(+) or 50 nM charybdotoxin + 50 nM apamin, suggesting that endothelium-derived hyperpolarizing factor (EDHF) is the participating dilator. The involvement of EDHF is further supported by experiments in which the relaxations of small mesenteric arteries are shown to be accompanied by membrane repolarization. These data strongly argue for a major role of a PKG-sensitive cation channel in modulating the release of EDHF from endothelial cells in rat small mesenteric arteries.